KEDUDUKAN DIALEKTOLOGIS BAHASA SAMBORI DALAM MASYARAKAT BIMA KONTEMPORER - Kamaludin Yusra; Yuni Budi Lestari; Nur Ahmadi; Muhammad Asyhar; Anang Zubaidi Soemerep (Masyarakat Linguistik Indonesia, 2016)
This article discusses phonological, morphological, syntactical and sociolinguistic aspects of the Sambori language spoken by the people of Sambori and its surroundings on Mount Lambitu, Bima, West Nusa Tenggara. The language and its cultures are in the endangered situation due to internal factors (for example due to mixed marriage and migration) and external factors (for example, due to economic, demographic and political pressures). The study documents the language by identifying its dialectological relation with the locally dominant Bima language and with other languages in the region (e.g. Samawa language and Sasak language). Identification was conducted by using elicitation, documentation, interview, and recording. Elicitation was performed in face-to-face interviews with respondents guided by a list of basic words and morphosyntactic forms. Documents were also collected from various forms of oral documents (e.g. folklores, stories, historical accounts and legends) in the language. Interviews were given to adult male and female speakers who are knowledgable of the language and its culture. The data were recorded by using tape recorders and digital cameras. Linguistic analysis was lexicostatistictal and the results show that the the Sambori language is a dialect of the Bima language with differences at the basic word level, but these differences follow predictable patterns of vowel and consonantal changes.